To solve the given equation \(0 = x^2 - 10x + 10\) by completing the square, we can follow these steps:
1) Completing the Square
Start with the equation:
\[ x^2 - 10x + 10 = 0 \]
First, we isolate the constant term on the right:
\[ x^2 - 10x = -10 \]
Next, we complete the square on the left side. To do this, take half of the coefficient of \(x\), which is \(-10\), and square it. Half of \(-10\) is \(-5\), and squaring it gives \(25\):
\[ x^2 - 10x + 25 = -10 + 25 \]
This simplifies to:
\[ (x - 5)^2 = 15 \]
Now, we have the equation in the completed square form:
\[ (x - 5)^2 = 15 \]
2) Finding the Solutions
Now, we solve for \(x\) by taking the square root of both sides:
\[ x - 5 = \pm \sqrt{15} \]
This gives us two solutions:
\[ x = 5 + \sqrt{15} \] \[ x = 5 - \sqrt{15} \]
Thus, the solutions can be expressed as:
\[ x = 5 \pm \sqrt{15} \]
Conclusion
The correct answer is:
(Choice B)
\[x = 5 \pm \sqrt{15}\]